BOOK REVIEW: HOW INTERNATIONAL LAW WORK A RATIONAL CHOICE THEORY - Mursal Maulana (Padjadjaran Journal of International Law, 2017)
Does international law affect state behavior?. Why would states pay any attention to international law in the absence of coercive enforcement mechanism?. What do we mean when we say international law is “binding”, given that states can almost always to violate it?. These intriguing and philosophical questions raised by the author to make sure that we had grasped at least one answer. If not, we were failed to understand the nature of international law. These question also remains us about traditional debate between proponent and opponent of international law such as Hobbes, Spinoza and Austin. But, in the 21st Century we are not debating or neglecting the existence of international law anymore.Written by Andrew T. Guzman who is recently serving as dean of The University of Southern California Gould School of Law (USC Gould), this book develops a persuasive explanation of why and when international law works by using rational choice perspective. Although previously there are some authors focusing their study on this topic such as Professor Abraham Chayes and Antonia Handler Chayes in their book “The New Sovereignty: Compliance with International Regulatory Agreement” which uses managerial approach in describing the compliance of international law and Professor Thomas Franck in his book “Fairness in International Law and Institution” which explains why states comply with international law by introducing fairness approach, this book offers better perspective in understanding international law in contemporary development by proposing “Rational Choice Theory”. The theory then is developed into “Three Rs of Compliance” (Reputation, Reciprocity and Retaliation). The book tries to explain how international law is able to affect state behavior despite a lack of coercive enforcement mechanism.